Determination of Some Minerals and Heavy metals in Raw Cow’s Milk - Küçük, Neslihan Yıldız; Gökçek, Ramazan (My University, 2024)
Milk is a healthy and nutritious food. Its ability to be consumed by all age groups and its easy accessibility increase the importance of milk in our diet. As technological developments increase, so does environmental pollution. As a result of this pollution, metals and metal mixtures reach animals and humans through the food chain. This situation negatively affects the health of living organisms. In addition, excessive intake of some mineral substances can also be toxic. The contamination of heavy metals in food occurs through various pathways. The risk of metals in the composition of the containers used in the production of acidic foods such as milk and cheese dissolving and passing into the product is more likely to occur than in other foods. For this purpose, in our research, 10 samples of raw cattle milk collected from different regions of Muş province were analyzed for the amounts of calcium, magnesium, sodium, potassium, zinc, iron, copper, manganese, and heavy metals lead and cadmium using Atomic Absorption Spectrometry device. The samples' lead, cadmium, iron, copper, and manganese contents were determined as 0.40±0.01-0.19±0.01, 0.38±0.00-0.20±0.00, 1.96±0.01-0.24±0.01, 0.50±0.00-0.11±0.00 and 0.20±0.00-0.12±0.00 mg/L, respectively. The highest levels of calcium (433.45±0.00 mg/L) and potassium (1146.25±0.02 mg/L) were detected in sample S10. The lowest levels of magnesium (197.81±0.00 mg/L) and sodium (661.17±0.01 mg/L) were found in sample S3. The zinc contents of the samples varied between 8.25±0.00-14.51±0.00 mg/L. The results obtained were evaluated considering the factors affecting the amount of mineral substances and heavy metal contamination in the milk.
Keywords: AAS; Heavy metal; Mineral content; Raw’s cow milk